Giovanni Pontano’s Aegidius: Humanistic Wisdom in Dialogue (Circe de clásicos y modernos, 2022)
The humanist Giovanni Giovano Pontano (1426-1503) wrote five dialogues, although only two of them (Charon and Antonius) were published during his lifetime. The last one, entitled Aegidius in honor of Giles of Viterbo, represents a conversation held in the context of the “Accademia Pontaniana” between a series of speakers who discuss the role of eloquence, the importance of combining sacred letters with profane ones, astrology, the immortality of the soul and the Aristotelian philosophical lexicon. We present an introduction to the main topics of this dialogue which accompany the Spanish translation of the Aegidiusincluded in this issue.
Keywords: Pontano; Aegidius; humanism; dialogue; rhetoric